Development of a novel series of non-natural triaryl agonists and antagonists of the Pseudomonas aeruginosa LasR quorum sensing receptor. Issue 1 (1st January 2017) - Capilato, Joseph N.; Philippi, Shane V.; Reardon, Thomas; McConnell, Ashleigh; Oliver, Dylan C.; Warren, Amy; Adams, Jill S.; Wu, Chun; Perez, Lark J.
Graphical abstract: Abstract: Bacterial chemical communication, through a process called quorum sensing (QS), plays a central role in infection in numerous bacterial pathogens. Quorum sensing in Pseudomonas aeruginosa employs a series of small molecule receptors including the master QS regulator, LasR. In this study we investigate a non-natural triaryl series of LasR ligands using a combination of structure activity relationship studies and computational modeling. These studies have enabled the identification of key structural requirements for ligand binding and have revealed a new strategy for inducing the therapeutically relevant antagonism of LasR.